Revisiting the concepts of forensic accounting and corporate fraud. (1st January 2013) - Imoniana, Joshua Onome; Silva, Robson Maciel
Forensic accounting initiates the exercise of fire extinguishing in a burning business environment to restore comfort to the demanding parties. Toeing this line this study is aimed at analysing the concepts to date and present methodologies for its investigation. The main question being answered is what is the characteristic of forensic accounting that holds it as professional accountants' innovation to curb corporate accounting malpractices? Data gathered were analysed through icons that represent formalism in the theory of self re-production. Findings make us to conclude that the idea that frauds have been least detected by auditors begins to gain shape as auditors are more adequately trained to detect fraud. Noteworthy that the customary systematic methodology for auditing does not serve forensic accounting investigation rather, a tete-à-tete with the least ranking staff up to the CEO considered through a less structured approach is likely to assist in reaching the desired objectives.